From one to many : scaling up health programs in low income countries - Chowdhury, A. M. Raza; Smith, George B. (George Baxter), 1907-2003; Ahmed, Faruque (The University Press Limited, 2011)
Contributed papers submitted to the International Conference on Scaling Up Health Programs, held in Dhaka, Bangladesh, in Dec. 2008.